2013
DOI: 10.2147/ijgm.s51906
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in three rural communities of Ife North Local Government Area of Osun State, South West Nigeria

Abstract: BackgroundThe prevalence of hypertension is increasing rapidly in sub-Saharan Africa, but data are limited on hypertension prevalence. In addition, few population-based studies have been conducted recently in Nigeria on the prevalence and correlates of hypertension in both urban and rural communities. Therefore, we determined the prevalence of hypertension in adults in the three rural communities of Ipetumodu, Edunabon, and Moro, in South West Nigeria.Materials and methodsOne thousand adults between 15 and 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
(46 reference statements)
5
12
6
Order By: Relevance
“…The last published rural study on HTN was as far back as 1998 [7]. The 31.1% prevalence of HTN observed in the MHA is similar to the 31.0% reported in Cameroon by Kingue et al [10] and the 32.9% reported by Amoah [15] in semiurban Ghana but higher than that reported elsewhere [3, 7, 8, 12, 16, 17]. The different settings and methodologies could account for this difference.…”
Section: Resultssupporting
confidence: 69%
“…The last published rural study on HTN was as far back as 1998 [7]. The 31.1% prevalence of HTN observed in the MHA is similar to the 31.0% reported in Cameroon by Kingue et al [10] and the 32.9% reported by Amoah [15] in semiurban Ghana but higher than that reported elsewhere [3, 7, 8, 12, 16, 17]. The different settings and methodologies could account for this difference.…”
Section: Resultssupporting
confidence: 69%
“…Comparatively, the prevalence of hypertension in the current study is lower than the prevalence of hypertension (26.1%) observed in west Bengal rural community in 2017 [16]. Similarly, recent studies conducted in south western Nigeria also reported a slightly higher prevalence of (31.6%) [17], 20.8% [18] and 26.4%, similar higher prevalence of hypertension 28.3% [19] was reported in Ethiopia Open Journal of Applied Sciences and 32% in Ghana [20]. Although these studies were done in the general com-…”
Section: Prevalence Of Hypertensioncontrasting
confidence: 69%
“…Our study shows that there were strong significant correlations between weight, body mass index, waist circumference and systolic blood pressure as well as diastolic blood pressure among the teaching and non-teaching staff. These findings corroborate the study of Adebayo et al, [23] which indicated a trend towards increase prevalence of risk of hypertension in Nigeria. Furthermore, Adebayo et al, [23] reported increased body mass index (BMI) significantly increase blood pressure in adults and this was supported by other authors [24]- [27].…”
Section: Discussionsupporting
confidence: 92%
“…These findings corroborate the study of Adebayo et al, [23] which indicated a trend towards increase prevalence of risk of hypertension in Nigeria. Furthermore, Adebayo et al, [23] reported increased body mass index (BMI) significantly increase blood pressure in adults and this was supported by other authors [24]- [27]. Additionally, Adedoyin et al, [16] reported similar findings in which weight and BMI were significantly correlated with systolic blood pressure and diastolic blood pressure but the correlations were weak contrary to that found in this study.…”
Section: Discussionsupporting
confidence: 92%